Relasi Fenomena Struktural Sebagai Penghambat Pendidikan Anak di Pamekasan - Maimun Maimun; Dela Lindasari; Muhammad Jamaluddin (Edudeena: Journal of Islamic Religious Education)
Abstract: This research is motivated by the large number of early marriages that occur in Panaguan Village, Larangan Pamekasan, most of which have an impact on  their education and psychological aspects. This research aim to find out; first, the phenomenon and the relation among of them. Second, the implication of early marriage on education and the psychological  aspects of the child. This research uses the phenomenology qualitative methods. The results showed that: First, there are 3 phenomena of early marriage in Panaguan Village, Larangan Pamekasan,  including : 1) traditional, 2) pragmatic, and 3), structural. The structural phenomena becomes the dominan aspect. Second, the implication of early marriage is hindering formal education of the child, and feel anxiety, stress, and double burden for the women.